The impact of reducing and eliminating user fees on facility-based delivery: a controlled interrupted time series in Burkina Faso - Nguyen, Hoa Thi; Zombré, David; Ridde, Valéry; De Allegri, Manuela (Health policy and planning, 2018)
Abstract. User fee reduction and removal policies have been the object of extensive research, but little rigorous evidence exists on their sustained effects in